Experiencing affective interactive art. (6th October 2010) - Bialoskorski, Leticia S.S.; Westerink, Joyce H.D.M.; Van den Broek, Egon L.
The progress in the field of affective computing enables the realisation of affective art. This paper describes the affective interactive art system Mood Swings, which interprets and visualises affect expressed by a person. Mood Swings is founded on the integration of a framework for affective movements and a colour model. This enables Mood Swings to recognise affective movement characteristics as expressed by a person and display a colour that matches the expressed emotion. With that, a unique interactive system is introduced, which can be considered as art, a game, or a combination of both, as becomes apparent from evaluations.